The Use Of Youtube Channel For Improving The Student’s Self Confident On Speaking At MA AL-WASHLIYAH 67 - Mardin Silalahi; Cut Nabila (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
The aim of this research was to to analyze the effect of Using YouTube Channel’s media on students’s self confident in speaking at the tenth grade of MA Al Washliyah 67 Pematangsiantar. in the academic year 2021/2022. This research used quantitative approach with true experimental design. The data were obtained by using pretest and posttest. The data of the pretest and post- test of both groups were analyzed by using descriptive and inferential statistics (SPSS 26.0). The result of the research shows that the testing hypothesis of posttest scores was found that tcount = 7.837> ttable = 1.699 at the significance level a = 0.05 and degrees of freedom (df) = 29. So, H0 is rejected and Ha is accepted. It means that the Using of YouTube Channel media effect significantly on student self confident in speaking at MA Al Washliyah 67 Pematangsiantar in academic year 2021/2022